Students' errors in solving plane geometry problems: A Newman's error analysis approach - Naftali Marbun; Renata Siburian; Nabila Nasution; Syeila Fatiha; Reva Lenita Girsang; Artorito Sitorus; Muhammad Amin Fauzi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aims to analyze students' errors in solving plane geometry problems using Newman's Error Analysis (NEA), with a focus on identifying specific error patterns that hinder learning. Geometry is a fundamental component of mathematics, yet many students struggle to master concepts involving plane figures and the distance from a point to a line. This research employed a descriptive qualitative design with nine second-semester mathematics education students at Universitas Negeri Medan in the 2024/2025 academic year as subjects. Based on test results, three students with the lowest scores were selected for in-depth analysis. The research instruments consisted of essay- and context-based geometry problems, validated by expert lecturers and piloted for clarity. Data were collected from students' written responses and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed five categories of errors: reading, comprehension, transformation, process skills, and encoding. Among these, comprehension errors and process skills errors were the most dominant, reflecting students' difficulties in interpreting information and applying accurate solution procedures. This study contributes to the literature by providing detailed insights into students' error patterns in plane geometry and highlighting the value of NEA as a diagnostic tool to inform targeted instructional strategies and improve mathematics learning outcomes.